Vascular age and endothelial dysfunction in individuals living at high altitude - Díaz-Lazo, Aníbal (2019)
Objective: To determine the relationship between vascular age (VA) and endothelial dysfunction (ED) in adults living at more than 3,000 m.a.s.l. Materials and methods: An observational, descriptive, cross-sectional study was performed at the Hospital Regional Docente Clínico Quirúrgico Daniel Alcides Carrión, Huancayo - Peru, from January to December 2015. The VA was calculated using the Framingham Risk Score and the ED was evaluated with the flow-mediated dilation (FMD) test in the brachial artery. A p-value <0.05 was considered significant. Results: The study included 67 individuals (100 %), whose mean age was 55.3 ± 13.4 years (range: 30-74), out of which 41 (61.1 %) were women. The VA and the delta value were 57.9 ± 18.3 and 2.3 ± 9.3 years, respectively. Fifty-three point seven percent (53.7 %) (36 participants) had an increased VA and 22.3 % (15 participants) were older than age 10. Increasing age, hypertension and overweight were associated with higher cardiovascular risk. From age 40, VA progressively increases and is more common in men. Individuals with ED presented high cardiovascular risk (87.5 %) compared to those with normal endothelial function (12.5 %) (p = 0.007; OR: 8.52; 95 % CI: 1.7-41.4). There is an inverse relationship between VA and endothelial function (r = -0.437; p = 0.000). The higher the VA , the higher the ED, which is more frequent in men (Rho = -1.0; p <0.010). Conclusions: There is an inverse relationship between VA and ED. Determining the endothelial function could improve the stratification of cardiovascular risk in individuals living at high altitude and thus prevent cardiovascular events.